RF coil design for accurate parallel imaging on 13C MRSI using 23Na sensitivity profiles. Issue 3 (30th May 2022) - Sanchez‐Heredia, Juan D.; Olin, Rie B.; Grist, James T.; Wang, Wenjun; Bøgh, Nikolaj; Zhurbenko, Vitaliy; Hansen, Esben S.; Schulte, Rolf F.; Tyler, Damian; Laustsen, Christoffer; Ardenkjær‐Larsen, Jan H.
Abstract : Purpose: To develop a coil‐based method to obtain accurate sensitivity profiles in 13 C MRI at 3T from the endogenous 23 Na. An eight‐channel array is designed for 13 C MR acquisitions. As application examples, the array is used for two‐fold accelerated acquisitions of both hyperpolarized 13 C metabolic imaging of pig kidneys and the human brain. Methods: A flexible coil array was tuned optimally for 13 C at 3T (32.1 MHz), with the coil coupling coefficients matched to be nearly identical at the resonance frequency of 23 Na (33.8 MHz). This is done by enforcing a high decoupling (obtained through highly mismatched preamplifiers) and adjusting the coupling frequency response. The SNR performance is compared to reference coils. Results: The measured sensitivity profiles on a phantom showed high spatial similarity for 13 C and 23 Na resonances, with average noise correlation of 9 and 11%, respectively. For acceleration factors 2, 3, and 4, the obtained maximum g‐factors were 1.0, 1.1, and 2.6, respectively. The 23 Na profiles obtained in vivo could be used successfully to perform two‐fold acceleration of hyperpolarized 13 C 3D acquisitions of both pig kidneys and a healthy human brain. Conclusion: A receive array has been developed in such a way that the 13 C sensitivity profiles could be accurately obtained from measurements at the 23 Na frequency. This technique facilitates accelerated acquisitions for hyperpolarized 13 C imaging. The SNR performance obtained at the 13 C frequency, compares well to other state‐of‐the‐art coils for the same purpose, showing slightly better superficial and central SNR.